Analysis of the Clinical Efficacy of Probiotics from the Genus Bacillus During Orthodontic Correction in Patients with Chronic Periodontitis to Reduce the Risk of Complications - Symonenko, Р. В. (Actual Dentistry, 2024)
Despite modern medicine’s achievements, treating chronic periodontitis remains an extremely difficult task. Orthodontic correction, as a component of complex treatment, can, in some cases, significantly improve patients’ periodontal status. However, it also carries the risk of worsening oral hygiene, which can intensify the inflammatory process. Therefore, periodontal maintenance therapy and long-term observation are crucial for treatment success and long-term teeth preservation. Purpose: To substantiate the local application of an original medicinal composition based on highly dispersed silica gel and bacteria of the Bacillus subtilis B-7812(AX20) and Bacillus licheniformis IMB B 7811(EA22) strains to reduce the risk of complications during orthodontic correction in patients with periodontitis. Materials and methods.30 patients of the main group (16 women and 14 men) and 18 patients (10 women and 8 men) of the control group, aged 25 to 60 years with generalized periodontitis of 1–2 degrees of severity, who underwent orthodontic correction using bracket systems for a period of up to 2 months, were under observation. For patients of the main group, orthodontic correction was combined with local drug therapy in the form of independent rinses with the proposed medicinal composition of highly dispersed silica gel and bacteria of the Bacillus subtilis B-7812 (AX20) and Bacillus licheniformis IMB B-7811 (EA22) strains (0.02 kg of silica gel and 2.5 × 109 CFU of live microbial cells in equal parts) once a day for a month. Clinical efficacy was determined by determining periodontal status, and assessment of oral hygiene was determined using the following indices: PI (Ind.Russеl) periodontal index; GI (Ind.Silness-Loe) gingival index; IGS (Ind.Greene a.Vermillion) hygiene index. These indices were calculated before, after two weeks, after 1 month and 2 months during orthodontic treatment. Results of the study. Our observations showed that after 1 month in the main group, PI significantly decreased, on average, by 49.2% from the initial level, GI decreased by 48.4%, and IHS — by 63.4%. A positive effect was observed after 2 months of orthodontic treatment (and 1 month after using the proposed remedy): PI (Ind.Russеl) decreased by 1.85 times, GI (Ind.Silness-Loе) significantly decreased by 2.6 times, IHS (Ind.Greene a.Vermillion) — by 3 times. In the control group for comparison, PI decreased by 1.2 times, GI — by 1.6 times, and IHS — by 2.1 times compared to the initial state. Conclusions. The conducted studies showed that the proposed medicinal composition of silica gel and bacteria of strains B. subtilis B-7812(AX20) and B. licheniformis IMB B-7811(EA22) has a pronounced therapeutic effect on periodontal tissues and significantly improves the local hygienic status of patients with chronic periodontitis who undergo orthodontic correction with fixed appliances.